Air quality indices: A review of methods to interpret air quality status. (2021) - Suman,
Abstract: Urban air pollution is rapidly increasing in Indian cities. Different methods have been designed to calculate the air quality index in form of mathematical formula. Many studies have shown association between exposure of the population to air pollutants and its adverse health impact. But the formula designed by CPCB in 2014 is more robust to find out the air quality category. To provide the public, information for air pollution dangers, several governmental and municipal agencies developed air quality indices, as a timely information about the potential changes in air quality. In this paper review of air quality index shows how AQI constitutes as an effective method to estimate air pollution levels and risks and help the government in effective pollution control measures adopted for reduction of emissions from various sources.